Proposição de medidas favorecedoras à acessibilidade e mobilidade de pedestres em áreas urbanas . Estudo de caso : o centro de Fortaleza - Melo, Fábio Barbosa (2005)
Walk is the most used transportation mode by people in urban areas. However, the public space adapted for the use of fast modes, mostly automobiles, restricts this basic capacity of the people and turning walking into dangerous activity, due to vulnerability of the human body in collisions. This fact is proven by the high number of accidents with fatal victims involving pedestrians. The precarious conditions available for walkers in Brazilian cities, and in cities of the developing countries, hinder the pedestrians' accessibility and mobility, influencing in the process of social exclusion and in indicators like unemployment, illiteracy and malnutriti on. On the other hand, there are examples of actions implanted in Brazilian cities and abroad, to improve the condition of the walk in urban areas, and to attract more people to use this transport way. These actions can be adapted and applied in places with lacks in this kind of action type. This work has as objective to propose measures to improve the pedestrians' accessibility and mobility in urban areas, considering the interaction among the elements of the system of transports: the man, the road, the urban space and the vehicle, in the fields of the planning and of the public politics, of the infra-structural and operational projects and of the legislation (circulation’s control and operation). This way, it is possible to identify the pedestrians' difficulties and to define actions to contribute in the reduction of the number of pedestrian’ crashes and to increase the walkway’s conditions in urban areas. In this work, the proposals are defined to the Central Area of Fortaleza, C.E., Brazil, as implantation example.